(3OjhGf GdJdYaQjs - (3GdJdYaQj , eMeO Hf jhSa Hf eSYhO GdTjHGfj, TgGH GdOjf CHh YHO Gddg,J (B675 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdYGde jeOM Gdedc GdCTQa ehSi Hf Gdedc GdYGOd de CRd ecKQkG Ydjg GdSDGdG hLhGHkG eG YfOg dj Shi dG s
(3BNQgG (B:s
(3eG CYLd heG hcdJe HGdSgQ Lafj hMLHJe Yf ShGce fXQj eG CfG eLfhf HYTbj dce Ch Cfce CMSf gPG GdHTQ s
(3ZjQ eQJH Ydi GdbhGaj hGdehVhYGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B25s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B53 s
Keywords: (3GdCOHs